145k views
4 votes
Express the following in exponential notation:
(-13) X (-13).
35 times

1 Answer

7 votes

Answer:


(-13) * (-13) = (-13)^(2)


35 * 35 = 35^(2)

Explanation:

Given


(-13) * (-13)

Required

Express as an exponential notation


(-13) * (-13)

Apply the following law of indices


x^a * x^b = x^(a+b)

This gives:


(-13) * (-13) = (-13)^(1+1)


(-13) * (-13) = (-13)^(2)

The second complete is incomplete; However, I'll assume it is: 35 times 35


35 * 35

Using the same law applied in (1) above:


35 * 35 = 35^(1+1)


35 * 35 = 35^(2)

User Chicrala
by
4.9k points